A comprehensive review of mobile technology use in hospitality and tourism. Issue 6 (18th August 2018) - Law, Rob; Chan, Irene Cheng Chu; Wang, Liang
ABSTRACT: Mobile technology has become a necessity for tourists, both in their daily lives and during their travels. Considering the growing significance of mobile technologies, this study collected and analyzed 92 related articles published in hospitality and tourism journals to examine the state-of-the-art research in this field. The comprehensive review shows that most studies focus on the context of tourism experience and the hotel industry. These studies tend to adopt quantitative research methods and use theories from the field of information system as theoretical foundation. A few research themes are identified from the perspectives of both the suppliers and consumers. An overall disproportionate focus has been given by researchers, with more studies concentrating on consumers than on suppliers. In accordance with the findings of the literature review, a research agenda is proposed to guide future research on mobile technology use in the hospitality and tourism industry.